Public health impact of recombinant zoster vaccine for prevention of herpes zoster in US adults immunocompromised due to cancer - Desmond Curran; Brandon J. Patterson; Justin Carrico; Ahmed Salem; Elizabeth M. La; Stéphane Lorenc; Katherine A. Hicks; Sara Poston; Christopher F. Carpenter (Taylor & Francis Group, 2023)
Individuals who are immunocompromised (IC) due to therapy or underlying disease are at increased risk of herpes zoster (HZ). This study evaluates the public health impact of recombinant zoster vaccine (RZV) relative to no HZ vaccination for the prevention of HZ among adults aged ≥18 years diagnosed with selected cancers in the United States (US). A static Markov model was used to simulate three cohorts of individuals who are IC with cancer (time horizon of 30 years; one-year cycle length): hematopoietic stem cell transplant (HSCT) recipients, patients with breast cancer (BC; a solid tumor example), and patients with Hodgkin's lymphoma (HL; a hematological malignancy example). Cohort sizes reflect the estimated annual incidence of each condition in the US population (19,671 HSCT recipients, 279,100 patients with BC, and 8,480 patients with HL). Vaccination with RZV resulted in 2,297; 38,068; and 848 fewer HZ cases for HSCT recipients, patients with BC, and patients with HL, respectively (each versus no vaccine). Vaccination with RZV also resulted in 422; 3,184; and 93 fewer postherpetic neuralgia cases for HSCT, BC, and HL, respectively. Analyses estimated the quality-adjusted life years gained to be 109, 506, and 17 for HSCT, BC, and HL, respectively. To prevent one HZ case, the number needed to vaccinate was 9, 8, and 10, for HSCT, BC, and HL, respectively. These results suggest RZV vaccination may be an effective option to significantly reduce HZ disease burden among patients diagnosed with selected cancers in the US.